(3GdefXeGJ GdOhdjI hGdEbdjejI hGdeJNUUI (B:s (3OQGSI aj YUHI GdCee GdeJMOI hGdLGeYI GdYQHjI hefXeI GdhMOI GdEaQjbjI hefXeI GdUMI GdYGdejI hLeYjI GdgdGd GdCMeQ GddjHj (B/s - (3GdTcQj, Ydj jhSas ((3GdbGgQI(B: s (3GjJQGc ddfTQ(B, s, 2003)
(3fTCI GdefXeGJ GdOhdjI hTNUjJgG GdbGfhfjI, GdefXeGJ GdOhdjI(B((3GdCee GdeJMOI(B)(3, GdefXeGJ GdEbdjejI, GdefXeGJ GdOhdjI GdeJNUUI(B((3efXeI GdUMI GdYGdejI(B)(3, GdefXeGJ ZjQ GdMchejIs
Keywords: (3GdefXeGJ GdGbdjejIs; (3GdefXeGJ GdOhdjIs; (3GdefXeGJ GdOhdjI GdGbdjejIs